Growth, Laser Raman, Thermal, Edax and Photoluminescence Studies of Pure and Calcium Doped Zinc Hydrogen Phosphate Crystals Using Single Diffusion Technique (Journal of Coating Science and Technology, 2017)
Growth aspects of pure and Calcium doped Zinc hydrogen phosphate single crystals from silica gel by the process of single diffusion technique are discussed. Crystals with different morphologies and effect on various parameters like gel pH, and gel ageing, gel density and concentration of reactants on the growth of pure and Calcium doped ZnHPO4 crystals were studied. Laser Raman spectra of the pure and Calcium doped ZnHPO4 crystals are recorded and the vibrational assignments have been made with possible explanations. Thermo gravimetrical analysis is undertaken to study the thermal stability of the grown crystals. The photoluminescence measurement shows that the material is suitable for photonic devices. The crystals grown were characterized by Laser Raman spectrum, TG/DTA, EDAX and Photoluminescence.